Unique Mobile Apps for Medical Learning: How Not to Fall Down Alice's Rabbit Hole. Issue 2 (3rd April 2019) - A. Becker, Danielle
Abstract: Libraries and medical libraries should strive to become well-versed in mobile apps because they are dynamic tools that actively engage users in learning and are outstanding reference resources. Mobile apps are one of many resources that health care professionals interested in teaching and learning should use to bolster their understanding of medical material. For new students, residents, physicians, nurses, and other health care professionals, being well-informed about existing and emerging mobile apps for learning is a vital tool for knowledge acquisition.